Google sites-based learning content development to promote self-directed learning in hybrid higher education: an addie-based study - Jumiati Siska; Muhammad Kristiawan; Elsa Viona (Jurnal Konseling dan Pendidikan, 2026)
The shift toward hybrid learning in higher education necessitates structured digital content that promotes student independence. This study developed and evaluated Google Sites-based digital learning content to support independent learning in an Educational Technology Literacy course. Using a Research and Development approach guided by the ADDIE model, the content was designed, validated, and implemented with 32 undergraduate students. Expert validation scores were 92.5% for content and 90.3% for media, indicating high validity. Student practicality assessments averaged 88.6%, and the mean independent learning score was 86.4%. Findings show that Google Sites is a feasible, low-cost platform for developing effective content that enhances learner autonomy in hybrid settings. This study provides practical implications for instructors seeking accessible solutions to support self-directed learning. The ADDIE-based development process offers a replicable framework for designing similar content in other courses. Institutions may incorporate Google Sites into digital strategies to enhance autonomy, especially where sophisticated systems are limited. The novelty lies in integrating Google Sites with the ADDIE model to foster self-directed learning in a hybrid context. While previous studies explored various platforms, limited research has systematically examined Google Sites as a primary content delivery tool evaluated through expert validation, student practicality, and independent learning outcomes. This study contributes theoretically by enriching self-directed learning literature and practically by offering a validated development model and evidence that such content enhances student autonomy in resource-constrained environments.